Pengukuran Skala Body Image dan Edukasi Kesehatan Stop Body Shamming pada Remaja - Iskandar, Yustiana Olfah; Siswati, Tri; Palestin, Bondan; Azizah, Ellen Nur; Sari, Anisa Kartika (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
Adolescence is a period of life transition from children to adults. In this periodes there are many changes in both emotional, physical condition, interests, and behavior patterns. The changes that occur often make teenagers not ready to understand so that self-dissatisfaction occurs. The existence of self-dissatisfaction with one's physical condition causes negative feelings to arise so that one considers a non-ideal physical condition as a deficiency. This will trigger teenagers to do body shaming. If the stigma of body shaming is not immediately eradicated, it will result in teenagers being prone to mental health disorders such as anxiety and prone to stress. In addition, adolescents are also prone to obesity and cardiovascular disease due to psychological conditions experienced. By looking at these problems, community service is carried out which aims to determine body image in adolescents so that it is hoped that body shaming actions can be prevented. Community service activities were carried out at SMA N 1 Tempel, attended by 128 students from first grade of high school. Activities carried out in the form of filling out the body image scale using a g-form questionnaire and providing education on the prevention of Body Shamming to students. The results of the questionnaire showed that the body shamming that occurred in SMA N 1 Tempel adolescents was in the less category as much as 55%. With sufficient knowledge, it is hoped that adolescents will be able to have a good self-concept and be able to make efforts to prevent body shaming.